EFEKTIFITAS AROMA TERAPIESSENSIAL OIL ROSE DALAMMENURUNKANSKALANYERIPADAPASIENKANKER STADIUM II - Annisa1, Husnah Suri; Huda, Nurul ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this researchwas to identify the effect of essential oil rose aromatherapy to decrease pain of the patient’s cancer stage II. This research was quasyexperiment method by used pretest and posttestdesigns with control group. It was conducted in Awal Bros Hospital and Islamic of Ibnu Sina HospitalPekanbaruwith 30 respondents, 15 peoples in the experimental group and 15 others in control group with purposivesampling technique. This reserach instrument used by observation sheet.It used univariate and bivariate analysis that Wilcoxon and MannWhitneytest.The results showed that there was significant difference between pain after given of essentialoilrose for experimental group and not given for control group (p value 0,000 < α 0,05). This research  wasrecommended of healthy institution for applicated as one of non farmachology therapy to decrease pain especially for patient’s cancer stage II. Keywords: Aromatheraphy, essential oil rose, the cancer patients stage II